(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : This research moved from the initial observation that the role of village heads in ruralcommunity development Wambo District of Gupura not going according to the expectations of society. Thus,this study aims to determine how the role of village heads in rural community development in the village ofthe District Wambo Gupura Lanny Jaya regency.By applying the methods of descriptive and qualitative approach, the informant taken as many as 10persons from the village officials and members of the BPD, then conducted in-depth interviews and theresults are analyzed by applying interactive techniques. The research results can be presented as follows: (1)That the general role of village heads in government affairs, development and community development inrural villages Wambo going pretty well, although not achieve optimal results. (2) That there are still someprograms / village development plans that can not be realized. This is due to the adequacy of the developmentbudget is still low, as well as bureaucratic obstacles, span of control and geographical conditions of ruralareas difficult to reach so ADD and Special Autonomy Fund p are experiencing delays.Advice can be given, among other things: to optimize the role of village heads in the implementationof rural development, it is suggested that local governments, especially Lanny Jaya regency governmentneeds to be allocated compensation in the form of performance benefits for the village chief achievers foreach month; and to ensure the realization of all the plans / programs of rural development, particularly inthe village of Wambo, it is recommended that in the preparation and adoption of program / villagedevelopment plans need to take into consideration the financial capacity of rural finance program / plan tobuild the village.Keywords: Role of the Village Head, Development of rural communities